2016
DOI: 10.3389/fnins.2016.00434
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Toluene and Ethanol on Dopaminergic Neurons of the Ventral Tegmental Area

Abstract: Drugs of abuse increase the activity of dopaminergic neurons of the ventral tegmental area (VTA), and output from the VTA is critical for both natural and drug-induced reward and reinforcement. Ethanol and the abused inhalant toluene both enhance VTA neuronal firing, but the mechanisms of this effect is not fully known. In this study, we used extracellular recordings to compare the actions of toluene and ethanol on DA VTA neurons. Both ethanol and toluene increased the firing rate of DA neurons, although tolue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…We have demonstrated previously that ethanol-induced excitation of VTA DA neurons in our recordings is unaltered by GABAergic or glutamatergic antagonists [ 90 ]. In the present study, we also found that the enhancement of ethanol-stimulated firing of VTA DA neurons by E2 is not altered by GABA receptor antagonists.…”
Section: Discussionmentioning
confidence: 97%
“…We have demonstrated previously that ethanol-induced excitation of VTA DA neurons in our recordings is unaltered by GABAergic or glutamatergic antagonists [ 90 ]. In the present study, we also found that the enhancement of ethanol-stimulated firing of VTA DA neurons by E2 is not altered by GABA receptor antagonists.…”
Section: Discussionmentioning
confidence: 97%
“…While these studies illuminate the variety of systems affected by ethanol, they do not address the primary response to ethanol, i.e., increased VTA neuron firing rate and increased dopamine release. However, ethanol excitation of DA VTA neurons is not diminished by dissociating the neurons from synaptic and glial connections (Brodie et al 1999 ), nor by the presence of antagonists of GABA A , GABA B , NMDA, AMPA, metabotropic glutamate, muscarinic or nicotinic cholinergic receptors (Nimitvilai et al 2016 ), indicating that these receptors are not necessary for the excitatory action of ethanol on DA VTA neurons in vitro. Although the specific target of ethanol action responsible for excitation of DA VTA neurons has not been identified, from a therapeutic standpoint, it is not necessary that a receptor or ion channel be the primary target of ethanol to have an important influence on the rewarding action of alcohol.…”
Section: Ethanol Actions On the Ventral Tegmental Areamentioning
confidence: 99%
“…HDAC inhibition also reversed morphine-induced changes in DA VTA activity (Authement et al 2016 ). The volatile organic solvent toluene is another addictive drug that shares physiological effects with other drugs of abuse, including alcohol (Nimitvilai et al 2016 ). Repeated toluene exposure altered acetylation of H3 in NAc and H4 in the VTA (Sanchez-Serrano et al 2011 ).…”
Section: Epigenetic Actions Of Ethanol: a Novel Avenue For Treatmentmentioning
confidence: 99%
“…To determine whether the reduction in CPP observed following CNO injection was due to nonspecific CNO-induced changes in exploratory behavior (MacLaren et al, 2016), the number of chamber entries for each animal following injection of saline or CNO were compared. There was no difference in chamber entries between air-exposed hM4Di DREADD-expressing rats following an injection of saline vehicle (109.3 Ϯ 11.6) or CNO (103.5 Ϯ 10.4; CNO effect: t (7) ϭ 0.65, p ϭ 0.54).…”
Section: Selective Manipulation Of Il-nac Physiology Attenuates Toluementioning
confidence: 99%
“…Controlling for potential off-target effects of CNO Although CNO activation of DREADDs has been used extensively to analyze circuit-specific control of various behaviors (Roth, 2016), findings from a recent study suggest that CNO metabolites, including clozapine, produce off-target effects, such as locomotor deficits, that may confound interpretation of the data (MacLaren et al, 2016;Gomez et al, 2017). This is of particular concern when studying drugs of abuse, such as psychostimulants, where enhanced locomotor activity is a notable effect of the drug.…”
mentioning
confidence: 99%